Psychological Factors, Classroom Environment and Teaching Methods as Correlates of Senior Secondary School Students’ Learning Outcomes in English Reading Comprehension in Ondo State (2012)
English Language is the medium of instruction in secondary schools in Nigeria and as a global language, it enables students to communicate effectively with the wider world. Reading comprehension is one of the important skills in English Language and learners‘ academic attainments depend largely on their level of competence in it. However, available data shows that students‘ persistent failure in it could be attributed to their lack of factual and contextual knowledge of the target skill, personal characteristics and methods adopted by the teachers. Based on this, it becomes imperative to examine variables that contribute to students‘ learning outcomes in English Reading Comprehension. Therefore, this study examined the correlates of psychological factors, classroom environment and teaching methods in students‘ learning outcomes. The study was a correlational research. Multistage sampling technique was adopted in selecting seven local government areas across the three senatorial zones in Ondo state. A teacher of English language from each of the 54 selected schools and a total of 2,055 students participated in the study. Six research questions were formulated and answered. Data were collected using six valid and reliable instruments: Reading Anxiety Scale (r=0.91), Reading Motivation Scale (r=0.94), Students‘ Attitude towards English Reading Comprehension Scale (r=0.88), English Reading Comprehension Classroom Environment Observational Checklist (π= 0.88), English Reading Comprehension Teaching Methods Observational Scale (π= 0.86) and English Reading Comprehension Achievement Test (r=0.84). Data were analysed using descriptive statistics and multiple regression. Students‘ attitude towards English Reading Comprehension was high as 87.1% of the respondents agreed that Reading Comprehension was an important aspect of the English Language. The combination of the independent variables showed that there was a positive relationship among psychological factors (reading anxiety and reading motivation), classroom environment and 12 teaching methods (mastery learning, advanced organiser, problem solving, demonstration, laboratory, discovery, lecture, concept mapping, discussion, mental imagery, cooperative and questioning), and students achievement scores (R=0.381), F(15,1959)=22.156, p<0.05). The composite contributions of the independent variables showed strong positive relationship among the 15 independent variables on students‘ attitude; (r= 0.916, 83.9%, .839, F(15,1959) = 684,74; p<0.05). Among the variables that contributed relatively to students‘ achievement in order of significant magnitude of beta weights were mastery learning (β=0.152, t=6.490, p<0.05), mental imagery (β=0.091, t=3.736, p<0.05), classroom environment (β=0.096, t=3.728, p<0.05), questioning (β=0.068, t=2.902, p<0.05) and lecture (β=0.063, t=2.645, p<0.05). Those that had relative and significant contributions towards students attitudes were motivation (β=0.759, t=75.763, p<0.05), discovery (β=0.102, t=16.439, p<0.05), discussion (β=0.079, t=7.616, p<0.05) and mastery learning (β=0.065, t=6.144, p<0.05). Psychological factors, classroom environment and teaching methods are very important to students learning outcomes. Reading motivation could be increased with the provision of appropriate instructional materials by education stakeholders. Teachers of English Language should adopt teaching methods that will maximize competence of the learners given the variations in their verbal ability and background knowledge